(3NhGU Gddjehf heG jQcH efgs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3Cbhd (B: (3Ef GdbOeGA hEf cGfhG bO CaGOhfG GdCUhd GdJi jSJfHW HgG eYQaI LejY eG jMJGL Edi GSJfHGW eYQaJg ef bhi s
(3BNQgG (B:s
(3jYJUQ GddjehG (B((3cPG(B) (3YdiTF ef GdedM HbOQ hJfRY QZhJg Ke jTeS CQHYjf jhekG , hjJQc hjSJYed s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B81 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg QVG QGeHhQ (B(3167(2)) s
Keywords: (3GdWHs